Investigating the role of maternal heart rate variability in the onset of labor - Widatalla, Namareq; Keenan, Emerson; Palaniswami, Marimuthu; Khandoker, Ahsan (Frontiers in Medicine, 2025)
There are currently no measures to accurately predict the onset of labor at term. Currently, the onset of labor is anticipated based on the estimated due date (EDD), which is derived from the day of the last menstrual period or ultrasound-based anatomical information. However, the EDD is not intended to identify physiological factors which may result in the early onset of labor. Therefore, there is a need to identify potential biomarkers that are associated with the onset of labor to accurately predict the timing of delivery. In this exploratory study, we investigated the associations between maternal RR interval (mRRI), maternal heart rate variability (mHRV) features, and the onset of labor. A total of 37 participants were analyzed, including 25 with Electrohysterogram (EHG)-derived signals (age: 28 ± 5.9 years; gestational age (GA): 34 ± 2.7 weeks) and 12 with non-invasive electrocardiogram (NIFECG)-derived signals (age: 32 ± 4.5 years; GA: 38 ± 1.5 weeks). The association of mHRV with the onset of labor was quantified by calculating correlations with time to delivery, defined as the difference between GA at recording and GA at delivery. Correlation analysis revealed that several standard mHRV indices showed strong associations (r > 0.5) with time to delivery.